THE EFFECT OF PAINTING ART ON POST-OPERATIVE HOPELESSNESS AND FATIGUE IN BREAST CANCER PATIENTS / A SEMI-EXPERIMENTAL STUDY - DOĞAN, Runida; ÖZKAN, Meral (Göbeklitepe Medical Science Journal, 2022)
Hopelessness and fatigue are common symptoms experienced by breast cancer patients in the post-operative period. Supportive interventions, such as art making or art therapy, are reported to have a positive effect on the symptoms experienced by cancer patients.This semi experimental study aims to evaluate the effect of painting on post-operative hopelessness and fatigue in breast cancer patients. The population of the study consisted of all adult patients who had surgery for breast cancer in a university hospital in Turkey and lived in the city center. The sample of the study consisted of 110 patients, 55 in the experimental group and 55 in the control group. The sample included patients who were selected through the improbable random sampling method. The research was completed between April 2016 and January 2018. Patient Information Form, Piper Fatigue Scale and Beck Hopelessness Scale were used to obtain data. Percentage, mean, standard deviation, chi-square, independent groups t test, paired t test and correlation were used in the analysis of the data. It was observed that the hopelessness and fatigue scores of the patients in the experimental group decreased statistically significantly after the painting study (p:0.000). No statistically significant change was observed in the hopelessness and fatigue scores of the patients in the control group. In this context, it is thought that nurses should know the effect of painting on hopelessness and fatigue and include it in their practices. It may be recommended to conduct new studies in order to evaluate the effects of painting on different patient groups.